Group Dynamics in the Cyberspace (Case Study on Komunitas Blogger Jogja and Loenpia Dot Net ) - Amalia, Ayu; Sukmono, Filosa Gita (Jurnal The Messenger, 2019)
Context of this study derived from communication studies, emphasizes on the perspective of a cultural shift as a result of the cyberspace phenomenon as an impact of the current-computing technology, and the changing patterns of information transmission and communication. Researchers conducted indepth interviews, towards the members of a bloggers community, such as 'Komunitas Blogger Jogja' (bloggerjogja.org), and 'Loenpia Dot Net' (loenpia.net/blog) which is a bloggers community based in Semarang.This research use qualitative analysis with descriptive approach.As results, group dynamics that are developed by each community, corresponds with the community character and nature, to maintain the self-existence. Member of bloggers community maintain the existence of his/her bloggers community, conducted by interacting on a regular basis amongst community members, as well as build awareness for the netizens by upload various information on his/her personal blog, linked with community web page.